The Yin–Yang Definition Model of Mental Health: The Mental Health Definition in Chinese Culture - Wang, Kai (Frontiers in Psychology, 2022)
It is a common concern of psychologists to construct a definition model with universal cultural adaptation for mental health. These models can be divided into two types in terms of definition: one is the negative mental health definition model based on the absence of mental illness symptoms; One is the definition model of positive mental health based on subjective feelings such as happiness and social identity. However, none of these definitions can properly explain Chinese people's understanding of mental health and their mental health practice under the Chinese cultural background. This paper proposed a Yin-Yang definition model of mental health based on the theory of personality of Confucianism and Taoism with a high integration character, this model can not only properly describe the Chinese understanding of mental health in traditional Chinese culture, but also explain east Asian psychotherapy and mental health practice in the context of Chinese culture, has the good cultural validity.